EFL Students’ Strategies in Relieving Anxiety in English Speaking Performances - Dena Suar Deni; Maskur Maskur; Alfiatunnur Alfiatunnur (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
performances. The kinds of strategies used by EFL students of English Education Department Ar-Raniry year of 2016 in reducing their stress in English speaking performances are expected to be used as a solution for the other EFL students in overcoming the anxiety in English speaking. The study is a quantitative method with a descriptive approach. The respondents of this study were 27 students of unit 02 English Education Department of Ar-Raniry year of 2016. The data obtained through a questionnaire. The items in the questionnaire adapted from Kondo and Ying-Ling (2004) and Robin K. Buchler (2013) research frameworks. The findings show the students cope with their anxiety by using some strategies, such as; Positive Thinking, Resignation, Peer seeking, Preparation, and Relaxation. The most strategy used by students is Preparation strategy, where the total number of them were used it. All of the strategies are expected can be used as the problem solver for the other EFL student.